2006
DOI: 10.1002/eji.200636682
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of NKG2D in CD4+ T cells specific for human cytomegalovirus

Abstract: The human NKG2D killer lectin‐like receptor (KLR) is coupled by the DAP10 adapter to phosphoinositide 3‐kinase (PI3 K) and specifically interacts with different stress‐inducible molecules (i.e. MICA, MICB, ULBP) displayed by some tumour and virus‐infected cells. This KLR is commonly expressed by human NK cells as well as TCRγδ+ and TCRαβ+CD8+ T lymphocytes, but it has been also detected in CD4+ T cells from rheumatoid arthritis and cancer patients. In the present study, we analysed NKG2D expression in human cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
101
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 61 publications
7
101
0
1
Order By: Relevance
“…Similarly, double-positive CD4+CD8+ T cells (Pawelec 1995), which generally contain a high proportion of memory and differentiated cells, were also increased in groups with worse functional status. CD4+NKG2D+ and CD4+CD8+ subsets have been associated with CMV infection; there was a significant correlation between their expansion and CMV infection and viral reactivation (Saez-Borderias et al 2006;Alonso-Arias et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, double-positive CD4+CD8+ T cells (Pawelec 1995), which generally contain a high proportion of memory and differentiated cells, were also increased in groups with worse functional status. CD4+NKG2D+ and CD4+CD8+ subsets have been associated with CMV infection; there was a significant correlation between their expansion and CMV infection and viral reactivation (Saez-Borderias et al 2006;Alonso-Arias et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…A recent report (38) suggested that a sizeable fraction of CMVspecific CD4 ϩ T cells expresses KIR (and NKG2D). In these experiments, PBMC were stimulated with IL-2 in the presence or absence of CMV, and KIR (and NKG2D) expression on CD4 ϩ T cells was measured after 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…The PRF1 gene is expressed primarily in NK cells and effector CD8 + T cells [31,32]. PRF1 is also expressed in a subpopulation of cytotoxic CD4 + T cells, which may combat various pathogens (33)(34)(35)(36)(37)(38)(39). An increased number of cytotoxic CD4 + T cells has been observed in patients with multiple sclerosis, rheumatoid arthritis, inflammatory bowel disease, and acute coronary syndromes [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%